2006
DOI: 10.1029/2005tc001809
|View full text |Cite
|
Sign up to set email alerts
|

Exhumation of basement‐cored uplifts: Example of the Kyrgyz Range quantified with apatite fission track thermochronology

Abstract: [1] The Kyrgyz Range, the northernmost portion of the Kyrgyzstan Tien Shan, displays topographic evidence for lateral propagation of surface uplift and exhumation. The highest, most deeply dissected segment lies in the center of the range. To the east, topography and relief decrease, and preserved remnants of a Cretaceous regional erosion surface imply minimal amounts of bedrock exhumation. The timing of exhumation of range segments defines the lateral propagation rate of the range-bounding reverse fault and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
134
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(142 citation statements)
references
References 57 publications
(87 reference statements)
7
134
1
Order By: Relevance
“…Similar reheating event observed in samples TK-09 and TK-10 was also reported from AFT thermal modelling of the sample 99WT-3, 7 km south of the Maidan fault (Sobel et al, 2006a), and in the Kyrgyz Range to the north and in the Aksu to the east Sobel et al, 2006b;Zhang et al, 2009). Finally, both models thus show an intense exhumation phase during the late Cenozoic (ca.…”
Section: Geomorphological Analysissupporting
confidence: 61%
See 2 more Smart Citations
“…Similar reheating event observed in samples TK-09 and TK-10 was also reported from AFT thermal modelling of the sample 99WT-3, 7 km south of the Maidan fault (Sobel et al, 2006a), and in the Kyrgyz Range to the north and in the Aksu to the east Sobel et al, 2006b;Zhang et al, 2009). Finally, both models thus show an intense exhumation phase during the late Cenozoic (ca.…”
Section: Geomorphological Analysissupporting
confidence: 61%
“…Oligocene-Miocene cooling ages corresponding to the onset of main deformation phase, which formed the modern Tian Shan, were detected along most of the sub-ranges except the southern flank of the Kyrgyz Range (Sobel et al, 2006a(Sobel et al, , 2006bDe Grave et al, 2007, 2010Zhang et al, 2009;Glorie et al, 2010Glorie et al, , 2011Chang et al, 2012;Macaulay et al, 2013Macaulay et al, , 2014Bande et al, 2014Bande et al, , 2015. AFT thermal modelling revealed a late Cenozoic reheating event along the Kyrgyz Range, Atbashi Range and Kokshaal Range, which might reflect sediment loading in this region or local tectonic burying in these regions (Sobel et al, 2006a(Sobel et al, , 2006b).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…For the northern Kazakh Tien Shan, De Grave et al (2013) reported Late Cretaceous and Neogene AFT ages for the Trans-Ili Range, and Late Jurassic-Early Cretaceous ages for the Zhetyzol Range. In the northern Kyrgyz Tien Shan, Early Cretaceous AFT ages are characteristic for the central Kungey Range, while many Early to Late Cretaceous AFT ages were obtained for the Terskey Range (De Grave et al, 2013;Macaulay et al, 2014;Sobel et al, 2006). Furthermore, in and around the Chinese part of the Ili Basin, Cretaceous AFT ages are reported by Jolivet et al (2010) and north of Lake Balkhash (in the Sayak ore field) Late Cretaceous AFT ages are reported by Chen et al (2012).…”
Section: Late Mesozoic Reactivationmentioning
confidence: 97%
“…Glorie et al, 2011b), the building of the modern Tien Shan is generally believed to have started in the Oligocene-early Miocene, and exhumation was widespread from the Miocene onwards (e.g. Bullen et al, 2001Bullen et al, , 2003Buslov et al, 2008;De Grave et al, 2013;Jolivet et al, 2010;Macaulay et al, 2013Macaulay et al, , 2014Sobel and Dumitru, 1997;Sobel et al, 2006;Yu et al, 2014). For example, Bullen et al (2001) reported AFT ages between 20 and 10 Ma for the Kyrgyz Range, in the northern Kyrgyz Tien Shan.…”
Section: Late Cenozoic Reactivationmentioning
confidence: 99%